Lithium ion battery and preparation method thereof, positive electrode sheet and power-using device
By using hydrogenated nitrile rubber and linear segment-containing compounds in the positive electrode active layer of lithium-ion batteries, the problems of positive electrode sheet brittleness and high diaphragm resistance are solved, and higher battery performance and stability are achieved.
Patent Information
- Application Number
- CN202411196004.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-29
AI Technical Summary
In traditional lithium-ion batteries, the positive electrode active layer of the positive electrode sheet has cracked due to poor brittleness, and the diaphragm resistance is high, which affects the performance of the battery.
The positive electrode active layer is introduced as a dispersant, and a compound containing linear segments is added as a softener, which can jointly reduce the brittleness of the positive electrode sheet, improve flexibility, and improve the dispersion of the material in the slurry, reduce the reduction of the brittleness of the positive electrode sheet, reduce the Gel, reduces the resistance of the diaphragm.
By improving the flexibility and dispersion of the positive electrode sheet, reducing cracking and diaphragm resistance, the first Coulomb efficiency and cycle capacity retention of lithium-ion batteries are improved.
Smart Images

Figure CN118693331B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a lithium-ion battery and a preparation method thereof, a positive electrode sheet and an electrical device. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] In recent years, the application scope of secondary batteries such as lithium-ion batteries has become increasingly wide, and they have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles and other fields. However, the positive active layer of the positive electrode sheet in traditional lithium-ion batteries has the problem of cracking due to poor brittleness, and the problem of high membrane resistance. Summary of the invention
[0004] In order to achieve the above-mentioned purpose, the present application provides a lithium ion battery and an electrical device comprising the lithium ion battery, wherein the positive electrode sheet in the lithium ion battery has good flexibility, is not easy to crack, and has low membrane resistance.
[0005] In a first aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active layer, and components of the positive electrode active layer comprise a positive electrode active material, a dispersant and a softener; the dispersant comprises hydrogenated nitrile rubber, and the softener comprises a compound containing linear segments.
[0006] The above-mentioned lithium-ion battery introduces hydrogenated nitrile rubber as a dispersant in the positive electrode active layer and introduces a compound containing linear segments as a softener. The linear segments in the softener can cooperate with the butadiene structural units in the hydrogenated nitrile rubber to reduce the brittleness of the positive electrode and improve the flexibility. At the same time, it can also effectively improve the dispersibility of the material in the slurry, reduce gel, and thus reduce the membrane resistance of the lithium-ion battery.
[0007] In some embodiments, the linear segment includes a copolymer segment of one or more of a C6~C18 alkyl group, an aryl-O-C6~C36 alkyl group, a polar group-substituted C2~C18 alkyl group, a polar group-substituted-O-C6~C24 alkyl carbon chain, a polyether segment, a polyamine segment, and a polysiloxane segment.
[0008] In some embodiments, the polar groups independently include one or more of an ester group, an amide group, a carbamate group, a carboxyl group, a hydroxyl group, and an amine group.
[0009] By using a flexible agent with a suitable structure, the flexibility of the positive electrode sheet can be further improved, cracking can be reduced, the membrane resistance can be reduced, and the initial coulombic efficiency and cycle capacity retention rate of the lithium-ion battery can be increased. Furthermore, by reasonably controlling the length of the linear segment in the flexible agent (each n value), lower brittleness and membrane resistance of the positive electrode sheet, as well as higher initial coulombic efficiency and cycle capacity retention rate can be obtained.
[0010] In some embodiments, the softener comprises a polyether segment having the following structural features:
[0011]
[0012] Wherein, R1 each independently includes C1~C18 alkyl or C6~C12 aryl;
[0013] G1 and G2 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group or a hydroxyl group;
[0014] 10≤n1≤500.
[0015] In some embodiments, the softener comprises a polyamine segment having the following structural features:
[0016]
[0017] Wherein, R2 each independently includes C1~C18 alkyl or C6~C12 aryl;
[0018] R3 each independently includes H, C1~C18 alkyl or C6~C12 aryl;
[0019] G3 and G4 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group or an amine group;
[0020] 10≤n2≤500.
[0021] In some embodiments, the softener comprises a copolymer segment of a polyamine segment and a polyether segment, and has the following structural features:
[0022]
[0023] Wherein, R4 each independently includes C1~C18 alkyl or C6~C12 aryl;
[0024] R5 each independently includes H, C1~C18 alkyl or C6~C12 aryl;
[0025] R6 each independently includes C1~C18 alkyl or C6~C12 aryl;
[0026] G5 and G6 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group, a hydroxyl group or an amine group;
[0027] 10≤n 3+ n4≤500.
[0028] In some embodiments, the softener comprises a polysiloxane segment having the following structural features:
[0029]
[0030] Wherein, R7 and R8 each independently include C1~C18 alkyl, C6~C12 aryl, polyether segment or polyoxyethylene ether polyoxypropylene ether copolymer segment;
[0031] G7 and G8 each independently include a C1~C18 alkyl group, a C6~C12 aryl group, a hydroxyl group or an amine group;
[0032] 10≤n5≤500.
[0033] In some embodiments, the compound comprises heteroatoms, and the heteroatoms include one or more of O, N and P.
[0034] In some embodiments, the mass ratio of the flexibilizer to the dispersant is 10:1 to 1:10. Reasonable control of the mass ratio of the two can take into account both lower diaphragm resistance and better electrode flexibility. Furthermore, the mass ratio of the flexibilizer to the dispersant is 3:1 to 1:3.
[0035] Furthermore, reasonable control of the weight average molecular weight, hydrogenation ratio, molar ratio of acrylonitrile structural units, etc. of the hydrogenated nitrile rubber can improve the dispersion stability of the slurry, reduce the diaphragm resistance, and make the electrode have better flexibility.
[0036] In some embodiments, the hydrogenated nitrile rubber has at least one of the following characteristics (1) to (3):
[0037] (1) Weight average molecular weight is 500~1000000;
[0038] (2) The hydrogenation ratio is 10%~100%;
[0039] (3) The molar proportion of acrylonitrile structural units is 5%~30%.
[0040] In some embodiments, the hydrogenated nitrile rubber has at least one of the following characteristics (1) to (3):
[0041] (1) Weight average molecular weight is 1000~200000;
[0042] (2) The hydrogenation ratio is 30%~50%;
[0043] (3) The molar proportion of acrylonitrile structural units is 10%~20%.
[0044] In some embodiments, the mass percentage of the softener in the positive electrode active layer is 0.05% to 0.5%.
[0045] In some embodiments, the positive electrode active material comprises one or more of lithium transition metal oxides and olivine-structured lithium-containing phosphates.
[0046] In some embodiments, the lithium transition metal oxide includes one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and modified compounds thereof; and / or
[0047] The lithium-containing phosphate with an olivine structure includes one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0048] In some embodiments, the components of the positive electrode active layer further include a binder.
[0049] In some embodiments, the binder has at least one of the following features (1) to (2):
[0050] (1) The binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin;
[0051] (2) In the positive electrode active layer, the mass percentage of the binder is 1% to 2.5%.
[0052] In a second aspect of the present application, a method for preparing a lithium-ion battery is provided, comprising the steps of preparing a positive electrode active layer:
[0053] Mixing components of a positive electrode active layer and a solvent to prepare a positive electrode slurry; the components of the positive electrode active layer include a positive electrode active material, a dispersant and a flexibilizer; the dispersant includes hydrogenated nitrile rubber, and the flexibilizer includes a compound containing a linear segment;
[0054] The positive electrode slurry is molded to prepare the positive electrode active layer.
[0055] In some embodiments, the step of mixing the components of the positive electrode active layer and the solvent comprises:
[0056] Firstly, the dispersant, the softener and part of the solvent are mixed, and then the obtained mixture is mixed with the remaining components; wherein the solid content of the mixture is 5% to 75%.
[0057] In some embodiments, the solid content of the mixed material is 7% to 20%.
[0058] In some embodiments, the components of the positive electrode active layer include a positive electrode active material, a dispersant and a flexibilizer; the dispersant includes hydrogenated nitrile rubber, and the flexibilizer includes a compound containing a linear segment.
[0059] In some embodiments, the positive electrode plate is the positive electrode plate in the lithium-ion battery as described above.
[0060] In a third aspect of the present application, an electrical device is provided, comprising at least one of the lithium-ion battery as described above, the lithium-ion battery prepared by the preparation method as described above, and the positive electrode sheet as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0062] Figure 1 FIG. 1 is a schematic diagram of a lithium-ion battery according to an embodiment of the present application.
[0063] Figure 2 for Figure 1 An exploded view of a lithium-ion battery according to an embodiment of the present application is shown.
[0064] Figure 3 A schematic diagram of an electrical device using a lithium-ion battery as a power source according to an embodiment of the present application.
[0065] Description of reference numerals:
[0066] 10. Lithium-ion battery; 11. Housing; 12. Electrode assembly; 13. Cover plate; 20. Electrical device. DETAILED DESCRIPTION
[0067] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0068] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0069] The "range" disclosed in the present application can be limited in the form of a lower limit and an upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The range limited in this way can be including or excluding end values, and any end value can be included or not included independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0070] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0071] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0072] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0073] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0074] In this application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A includes not only a1, a2 and a3, but also other members".
[0075] In this application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0076] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0077] In the present application, the term "alkyl" refers to a monovalent residue formed by the loss of a hydrogen atom from a saturated hydrocarbon containing a primary (normal) carbon atom, a secondary carbon atom, a tertiary carbon atom, a quaternary carbon atom, or a combination thereof. A phrase containing the term, for example, "C1-C18 alkyl" refers to an alkyl containing 1 to 18 carbon atoms, and each occurrence can be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl, C9 alkyl, C10 alkyl, C11 alkyl, C12 alkyl, C13 alkyl, C14 alkyl, C15 alkyl, C16 alkyl, C17 alkyl, C18 alkyl (the meanings of the remaining alkyls of different carbon chain lengths are the same). Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(C H3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3-methyl-1-butyl (- CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH( 2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3 and octyl (-(CH2)7CH3).
[0078] In the present application, the term "aryl" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom, which can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. For example, "C6-C18 aromatic group" refers to an aromatic group containing 6 to 18 carbon atoms, and each time it appears, it can be independently C6 aromatic group, C7 aromatic group, C8 aromatic group, C9 aromatic group, C10 aromatic group, C11 aromatic group, C12 aromatic group, C13 aromatic group, C14 aromatic group, C15 aromatic group, C16 aromatic group, C17 aromatic group or C18 aromatic group (the meaning of the other aromatic groups with different carbon numbers is the same). Suitable examples include, but are not limited to: benzene, biphenyl, naphthalene, anthracene, phenanthrene, diphenylene, triphenylene and their derivatives.
[0079] In traditional methods, the positive electrode active layer of the positive electrode sheet in lithium-ion batteries usually uses hydrogenated nitrile rubber as a dispersant to improve the dispersion of each component in the slurry in order to reduce the membrane resistance, but the membrane resistance is still high. At the same time, the winding and pressing processing methods used in the production of lithium-ion batteries can easily cause the positive electrode active layer to crack due to poor brittleness. How to improve the flexibility of the positive electrode active layer and reduce cracking is also one of the problems that need to be solved urgently.
[0080] Some embodiments of the present application provide a lithium-ion battery, including a positive electrode plate, wherein the positive electrode plate includes a positive electrode active layer, and the components of the positive electrode active layer include a positive electrode active material, a dispersant and a softener; the dispersant includes hydrogenated nitrile rubber, and the softener includes a compound containing linear segments.
[0081] In the above lithium-ion battery, hydrogenated nitrile rubber is introduced as a dispersant in the positive electrode active layer, and a compound containing a linear segment is introduced as a flexibilizer. The linear segment in the flexibilizer can cooperate with the butadiene structural unit in the hydrogenated nitrile rubber to reduce the brittleness of the positive electrode and improve the flexibility. At the same time, it can also effectively improve the dispersibility of the material in the slurry, reduce gel, and thus reduce the membrane resistance of the lithium-ion battery. The possible reasons are speculated to be:
[0082] On the one hand, the linear segments in the softener and the butadiene structural units in the hydrogenated nitrile rubber are both flexible segments, and the linear structures of these flexible segments have less branching and lower rotational energy barriers, so they can be embedded in other components, such as the segments of the binder, to increase the material's slip ability, improve the flexibility of the positive electrode, and reduce the problem of cracking of the positive electrode active layer due to its poor brittleness.
[0083] On the other hand, the butadiene structural unit in hydrogenated nitrile rubber is an alkyl chain segment with a longer chain length and a certain degree of branching, and the linear segment in the softener is similar to it. The two can be fully expanded in the slurry solvent to produce a steric hindrance effect, reduce the proximity between material particles, and thus improve the dispersion of the material in the slurry, reduce gelation, and reduce the membrane resistance of lithium-ion batteries.
[0084] In addition, based on the reduction of membrane resistance, the initial coulombic efficiency and cycle capacity retention rate of lithium-ion batteries can be improved.
[0085] Furthermore, the problem of poor brittleness of the conventional positive electrode sheet is solved in thick-coated positive electrode sheets (the coating amount per unit area of the positive electrode active layer in the thick-coated positive electrode sheet is ≥300mg / 1540.25mm 2 ), by adopting the said softener, the brittleness of thick-coated positive electrode plates can be significantly improved and the flexibility can be improved.
[0086] Without limitation, the presence of hydrogenated nitrile rubber and compounds containing linear chain segments in the positive electrode active layer can be obtained by separating and purifying the materials of the positive electrode active layer (such as organic solvent extraction, thin layer chromatography column separation) to obtain hydrogenated nitrile rubber and polymers containing linear chain segments, and then confirmed by characteristic peaks in gas chromatography-mass spectrometry and infrared test spectra.
[0087] In some embodiments, the linear segment includes a copolymer segment of one or more of a C6~C18 alkyl group, an aryl-O-C6~C36 alkyl group, a polar group-substituted C2~C18 alkyl group, a polar group-substituted aryl-O-C6~C24 alkyl group, a polyether segment, a polyamine segment, and a polysiloxane segment. Further, the polar groups each independently include one or more of an ester group, an amide group, a carbamate group, a carboxyl group, a hydroxyl group, and an amine group. Introducing the above-mentioned polar group with a conjugated structure in the alkyl group can improve the conductivity of the flexibilizer, further reduce the membrane resistance of the lithium ion battery, and improve the cycle performance of the lithium ion battery. Without limitation, the polar group can be one or more than two. In some embodiments, the number of polar groups is 1~2.
[0088] In some embodiments, the softener comprises a polyether segment having the following structural features:
[0089]
[0090] Wherein, R1 each independently includes C1~C18 alkyl or C6~C12 aryl;
[0091] G1 and G2 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group or a hydroxyl group;
[0092] 10≤n1≤500. Further, 10≤n1≤50. Specifically, the value of n1 includes but is not limited to: 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range between any two of the foregoing.
[0093] In some embodiments, the softener comprises a polyamine segment having the following structural features:
[0094]
[0095] Wherein, R2 each independently includes C1~C18 alkyl or C6~C12 aryl;
[0096] R3 each independently includes H, C1~C18 alkyl or C6~C12 aryl;
[0097] G3 and G4 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group or an amine group;
[0098] 10≤n2≤500. Further, 10≤n2≤50. Specifically, the value of n2 includes but is not limited to: 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range between any two of the foregoing.
[0099] In some embodiments, the softener comprises a copolymer segment of a polyamine segment and a polyether segment, and has the following structural features:
[0100]
[0101] Wherein, R4 each independently includes C1~C18 alkyl or C6~C12 aryl;
[0102] R5 each independently includes H, C1~C18 alkyl or C6~C12 aryl;
[0103] R6 each independently includes C1~C18 alkyl or C6~C12 aryl;
[0104] G5 and G6 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group, a hydroxyl group or an amine group;
[0105] 10≤n 3+ n4≤500. Furthermore, 10≤n 3+n4≤50. Specifically, n 3+ The value of n4 includes, but is not limited to, 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range between any two of the foregoing.
[0106] In some embodiments, the softener comprises a polysiloxane segment having the following structural features:
[0107]
[0108] Wherein, R7 and R8 each independently include C1~C18 alkyl, C6~C12 aryl, polyether segment or polyoxyethylene ether polyoxypropylene ether copolymer segment; G7 and G8 each independently include C1~C18 alkyl, C6~C12 aryl, hydroxyl or amine; without limitation, in this structural feature, the polyether segment may have the following structure: , 2≤n6≤10, 2≤n7≤100, G9 includes C1~C18 alkyl or C6~C12 aryl; the polyoxyethylene ether polyoxypropylene ether copolymer segment may have the following structure: , 2≤n8≤50, 1≤n9≤50, G 10 Including C1~C18 alkyl or C6~C12 aryl;
[0109] 10≤n5≤500. Further, 10≤n5≤50. Specifically, the value of n5 includes but is not limited to: 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range between any two of the foregoing.
[0110] By adopting a flexible agent with a suitable structure, the flexibility of the positive electrode sheet can be further improved, cracking can be reduced, the membrane resistance can be reduced, and the initial coulombic efficiency and cycle capacity retention rate of the lithium-ion battery can be improved. Furthermore, by reasonably controlling the length of the linear segment in the flexible agent (each n value), lower brittleness and membrane resistance of the positive electrode sheet, as well as higher initial coulombic efficiency and cycle capacity retention rate can be obtained. It can be understood that in the structural characteristics of the above-mentioned flexible agent, the substituents in each structural unit can be the same or different. When different, it can be a copolymer of different structural units.
[0111] Without limitation, the structure of the softener can be obtained by separating and purifying the material of the positive electrode active layer (such as organic solvent extraction, thin layer chromatography column separation), and then confirmed by the characteristic peaks and peak areas in the gas chromatography-mass spectrometry, infrared test spectrum, and nuclear magnetic resonance test spectrum.
[0112] In some embodiments, the compound contains heteroatoms, and the heteroatoms include one or more of O, N and P. Introducing heteroatoms into the compound can better improve the overall flexibility of the positive electrode sheet and reduce cracking, which may be due to the presence of heteroatoms that can better destroy other components, such as hydrogen bonds between segments of the binder, and reduce its crystallinity.
[0113] Without limitation, N and P can be tested by phosphorus spectrum and nitrogen spectrum, and O atoms mainly come from ether bonds and can be calibrated by carbon spectrum and hydrogen spectrum of the linked C.
[0114] In some embodiments, the mass ratio of the softener to the dispersant is 10:1~1:10. There is a certain competitive relationship between the effects of the softener and the dispersant. The more linear segments, the better the flexibility, but the easier it is to aggregate, and vice versa. Reasonable control of the mass ratio of the two can take into account both lower diaphragm resistance and better electrode flexibility. Specifically, the mass ratio of the softener to the dispersant includes but is not limited to: 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or a range between any two of the foregoing. Furthermore, the mass ratio of the softener to the dispersant is 3:1~1:3.
[0115] Without limitation, the mass ratio of the softener to the dispersant can be separated by gas chromatography or thin layer chromatography to obtain their respective contents.
[0116] In some embodiments, the weight average molecular weight of the hydrogenated nitrile rubber is 500 to 1000000. Reasonable control of the weight average molecular weight of the hydrogenated nitrile rubber can reduce the intermolecular force and structural rigidity while having a certain number of flexible segments and cyano anchoring groups, which is conducive to its better dissolution and dispersion in the slurry, thereby improving the dispersion stability of the slurry, reducing the diaphragm resistance, and making the electrode have better flexibility. Specifically, the weight average molecular weight of the hydrogenated nitrile rubber includes, but is not limited to, 500, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 100000, 200000, 250000, 300000, 350000, 400000, 450000, 500000, 600000, 1000000 or a range between any two of the foregoing. Further, the weight average molecular weight is 1000-200000.
[0117] Without limitation, a Waters 2695 Isocratic HPLC gel chromatograph (differential refractive index detector 2141) was used. A polystyrene solution sample with a mass fraction of 3.0% was used as a reference, and a matching chromatographic column (oily: StyragelHT5 DMF7.8 300mm+Styragel HT4) was selected. A 3.0% polymer solution was prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution was allowed to stand for one day for use. During the test, tetrahydrofuran was first drawn with a syringe and rinsed, and repeated several times. Then 5 mL of the experimental solution was drawn, the air in the syringe was removed, and the needle tip was wiped dry. Finally, the sample solution was slowly injected into the injection port. The data was obtained after the indication was stable.
[0118] In some embodiments, the hydrogenation ratio of the hydrogenated nitrile rubber is 10% to 100%. Different hydrogenation ratios correspond to different ratios of double bonds. The ratio of double bonds affects the subsequent cross-linking of the polymer, and then affects the expansion of the flexible segments in the polymer in the slurry solvent and the size of the steric hindrance. Reasonable control of the hydrogenation ratio can further improve the dispersion stability of the slurry, reduce the membrane resistance, and make the pole piece have better flexibility. Specifically, the hydrogenation ratio of the hydrogenated nitrile rubber includes but is not limited to: 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or the range between any two of the foregoing. Further, the hydrogenation ratio is 30% to 50%.
[0119] It can be understood that the "hydrogenation ratio" means that the molar content of double bonds in the nitrile rubber is P1, and the molar content of double bonds in the hydrogenated nitrile rubber obtained after the corresponding hydrogenation is P2, then the hydrogenation ratio is (P1-P2) / P1. Among them, the nitrile rubber and the hydrogenated nitrile rubber obtained after its hydrogenation have similar structural units, for example, the molar ratio of butadiene structural units (including hydrogenated and unhydrogenated) and acrylonitrile is consistent. By detecting the molar ratio of butadiene structural units (including hydrogenated and unhydrogenated) and acrylonitrile in hydrogenated nitrile rubber, the corresponding nitrile rubber raw material can be reversely deduced, and then the P1 value can be obtained.
[0120] Without limitation, the double bond molar content can be tested by the iodine value method: weigh a certain amount of the test product, add chloroform to dissolve it, then add a certain amount of Wei's reagent (ICl), so that the test product and Wei's reagent react fully, after reaching the specified reaction time, add potassium iodide and water, and finally titrate with sodium thiosulfate until the yellow color almost disappears, then add starch solution, continue to titrate and shake vigorously until the blue color just disappears, and the amount of sodium thiosulfate used by titration can be used to calculate the double bond content in the test product. Repeat the test twice for the same sample according to the above test steps and take the average value.
[0121] In some of the embodiments, the molar proportion of the acrylonitrile structural unit in the hydrogenated nitrile rubber is 5% to 30%. The cyano group in the acrylonitrile structural unit acts as an anchoring group, which can be anchored with the positive electrode active material through coordination, thereby improving the dispersion performance. Reasonable control of the molar percentage can achieve a better anchoring effect while allowing the hydrogenated nitrile rubber to retain better flexibility, thereby further improving the dispersion stability of the slurry, reducing the diaphragm resistance, and making the pole piece have better flexibility. Specifically, the molar proportion of the acrylonitrile structural unit in the hydrogenated nitrile rubber includes but is not limited to: 5%, 10%, 15%, 20%, 25%, 30% or a range between any two of the foregoing. Further, the molar proportion of the acrylonitrile structural unit is 10% to 20%.
[0122] Without limitation, the molar proportion of the acrylonitrile structural unit in the hydrogenated nitrile rubber can be converted into free cyano groups by burning, and then the cyano groups are titrated and determined.
[0123] In some embodiments, the mass percentage of the softener in the positive electrode active layer is 0.05% to 0.5%. Reasonable control of the mass percentage of the softener in the positive electrode active layer can improve the flexibility of the electrode, while improving the dispersion stability of the slurry, reducing the membrane resistance, and also reducing the impact on the electrical properties of the lithium-ion battery (such as cycle performance). Specifically, the mass percentage of the softener in the positive electrode active layer includes but is not limited to: 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5% or a range between any two of the foregoing. Furthermore, the mass percentage of the softener in the positive electrode active layer is 0.2% to 0.4%.
[0124] Without limitation, the mass percentage of the softener in the positive electrode active layer can be obtained by separating and purifying the material of the positive electrode active layer (such as organic solvent extraction, thin layer chromatography column separation), and calculating the mass of the softener.
[0125] It is also understandable that the above-mentioned different types of flexibilizers and hydrogenated nitrile rubber can be obtained from the market, or can be synthesized by purchasing corresponding monomers (all of which are commercially available) according to traditional methods. For example, the synthesis method of hydrogenated nitrile rubber generally includes the following steps:
[0126] (1) Copolymerizing butadiene and acrylonitrile to prepare an intermediate;
[0127]
[0128] (2) The intermediate is subjected to Pd / C catalytic hydrogenation to prepare hydrogenated nitrile rubber.
[0129]
[0130] In this step, hydrogenated nitrile rubbers with different weight average molecular weights, hydrogenation ratios or molar proportions of acrylonitrile structural units can be prepared by controlling the ratio of butadiene to acrylonitrile, reaction temperature, reaction time, hydrogenation pressure, etc.
[0131] In some of the embodiments, the positive electrode active material may be a positive electrode active material for a battery known in the art. As a non-limiting example, the positive electrode active material may include one or more of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Non-limiting examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.8 Co 0.15 Al 0.05 O2. Furthermore, the positive electrode active material includes lithium iron phosphate. The cyano group is easy to coordinate with Fe in the lithium iron phosphate, thereby improving the stability and dispersibility of the slurry.
[0132] It can be understood that the lithium iron phosphate described in the present application may include the lithium iron phosphate material itself, and may also include a lithium iron phosphate product obtained by doping and / or coating the lithium iron phosphate material with trace elements.
[0133] In some embodiments, the particle size D50 of the positive electrode active material is 0.2 μm to 20 μm.
[0134] In some embodiments, the positive electrode active layer further includes a binder.
[0135] As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. Further, the binder includes polyvinylidene fluoride. Using polyvinylidene fluoride as a binder can achieve better flexibility. It is speculated that the possible reason is that linear segments and butadiene structural units are easier to insert into the segments of polyvinylidene fluoride, thereby improving its sliding ability and thus improving the flexibility of the pole piece.
[0136] In some embodiments, the mass percentage of the binder is 1% to 2.5%.
[0137] In some other embodiments of the present application, a method for preparing a lithium-ion battery as described above is provided, comprising the steps of preparing a positive electrode active layer:
[0138] Mixing components of a positive electrode active layer and a solvent to prepare a positive electrode slurry; the components of the positive electrode active layer include a positive electrode active material, a dispersant and a flexibilizer; the dispersant includes hydrogenated nitrile rubber, and the flexibilizer includes a compound containing a linear segment;
[0139] The positive electrode slurry is molded to prepare the positive electrode active layer.
[0140] The preparation method has simple steps and is convenient for technological application.
[0141] Without limitation, the dispersant and the softener may be pre-mixed and then added to the other components, or may be added to the other components sequentially.
[0142] In some embodiments, the step of mixing the components of the positive electrode active layer and the solvent comprises:
[0143] Firstly, the dispersant, the softener and part of the solvent are mixed, and then the obtained mixture is mixed with the remaining components; wherein the solid content of the mixture is 5% to 75%.
[0144] Premixing the dispersant, the softener and part of the solvent and reasonably controlling the solid content of the mixture can improve the uniformity of the dispersion of the two in the slurry, which is conducive to the performance of their efficacy. Specifically, the solid content of the mixture includes but is not limited to: 5%, 7%, 10%, 13%, 15%, 17%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or a range between any two of the foregoing.
[0145] Without limitation, the solid content can be tested by the following method: weigh the copper foil in a weight loss meter, record it as M0, and reset it to zero; take the mixed material, apply a small amount on the copper foil, and then weigh it in a moisture meter, record it as M1; close the equipment and start drying; after the end, record the weighing data, record it as M2, and calculate the solid content, the solid content is (M2-M0) / (M1-M0).
[0146] Another embodiment of the present application provides a lithium-ion battery. The lithium-ion battery includes the above-mentioned positive electrode plate.
[0147] Another embodiment of the present application provides an electric device, which includes at least one of the above-mentioned positive electrode sheet and the above-mentioned lithium-ion battery.
[0148] The lithium-ion battery and the electrical device of the present application will be described below with reference to the accompanying drawings as appropriate.
[0149] Generally, lithium-ion batteries include a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0150] The positive electrode plate includes a positive electrode current collector and a positive electrode active layer arranged on at least one surface of the positive electrode current collector. The positive electrode active layer is as described above and will not be described in detail here.
[0151] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0152] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0153] In some embodiments, the positive electrode active material layer may further include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0154] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, polymer, conductive agent, binder and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt%~80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000mPa·s~25000mPa·s. When applying the positive electrode slurry, the coating unit surface density based on dry weight (excluding solvent) can be 15 mg / cm 2 ~35mg / cm 2 The compaction density of the positive electrode can be 3.0g / cm 3 ~3.6g / cm 3 , optional 3.3g / cm 3 ~3.5g / cm 3 .
[0155] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0156] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0157] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0158] In some of the embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0159] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0160] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0161] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0162] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000mPa·s~10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75g / m 2 ~220g / m 2 The compaction density of the negative electrode sheet can be 1.0g / cm 3 ~ 1.8g / cm 3 .
[0163] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0164] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0165] In some embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0166] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, )、ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate ( ), fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0167] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0168] In some embodiments, the additive in the electrolyte may include, but is not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.
[0169] In some embodiments, the lithium-ion battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0170] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0171] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may be 12 μm to 20 μm.
[0172] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.
[0173] In some embodiments, the lithium-ion battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0174] In some embodiments, the outer packaging of the lithium-ion battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium-ion battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0175] A lithium-ion battery includes at least one battery cell. A lithium-ion battery may include one or more battery cells.
[0176] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0177] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 A lithium-ion battery 10 having a square structure is used as an example.
[0178] In some embodiments, reference Figure 2 , the outer packaging may include a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the lithium-ion battery 10 can be one or more, and those skilled in the art can select according to actual needs.
[0179] The lithium-ion battery can be a battery module or a battery pack.
[0180] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.
[0181] In the battery module, the plurality of battery cells may be arranged in sequence along the length direction of the battery module. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells may be fixed by fasteners.
[0182] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of battery cells are accommodated in the accommodation space.
[0183] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.
[0184] The battery pack may include a battery box and a plurality of battery modules disposed in the battery box. The battery box includes an upper box body and a lower box body, and the upper box body can be covered on the lower box body to form a closed space for accommodating the battery modules. The plurality of battery modules can be arranged in the battery box in any manner.
[0185] In addition, the present application also provides an electrical device, which includes the lithium-ion battery provided in the present application. The lithium-ion battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited to these. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited to these.
[0186] As an electrical device, a lithium-ion battery can be selected according to its usage requirements.
[0187] Figure 3 The power consumption device 20 is taken as an example. The power consumption device 20 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or a battery module can be used.
[0188] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0189] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0190] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0191] The test methods involved in the embodiments are as follows:
[0192] (1) Positive electrode brittleness test:
[0193] Take a positive electrode sheet without obvious defects, cut it into samples with a length × width of 20cm × 2.5cm in the longitudinal direction, and the number of samples should be ≥ 8. After pre-folding it in half, place the film on the test platform and roll it once with a 2kg cylindrical roller. If it is light-transmitting, the number of times of brittle light transmission is 1. If it is not light-transmitting, repeat the reverse folding and rolling. Observe the crease against the light to see if it is light-transmitting or broken, record the actual number of folds, and take the average as the test result.
[0194] (2) Diaphragm resistance (DCR) test:
[0195] Cut the dried positive electrode slurry (film layer) at the left, middle and right of the positive electrode sheet into small discs with a diameter of 3mm. Turn on the power of Yuanneng Technology's electrode sheet resistor meter, place the "probe" of the electrode sheet resistor meter in a suitable position, click the "Start" button, and wait for the reading to stabilize before reading. Test two positions of each small disc, and finally calculate the average value of six measurements, which is the resistance of the electrode sheet film layer.
[0196] (3) First Coulomb efficiency:
[0197] At 25°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 0.1C to a voltage of 3.65V. The charging capacity at this time was recorded as the first-cycle charging capacity of the lithium-ion battery. After that, they were allowed to stand for 5 minutes, and then discharged at a constant current of 0.1C to a voltage of 2.0V. The batteries were allowed to stand for 5 minutes. This was a charge and discharge cycle. The discharge capacity was recorded as the first-cycle discharge capacity of the lithium-ion battery, which was the initial capacity of the lithium-ion battery.
[0198] The first cycle coulombic efficiency of a lithium-ion battery (%) = first cycle discharge capacity / first cycle charge capacity × 100%.
[0199] (4) Cycle capacity retention rate:
[0200] At 45°C, the batteries in the examples and comparative examples were charged to 3.65V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 3.65V, left for 10 minutes, and then discharged to 2.5V at a constant current of 1 / 3C. The obtained capacity was recorded as the initial capacity C0. Repeat the above steps for the same battery, and record the discharge capacity C0 of the battery after the nth cycle. n , then the battery capacity retention rate after each cycle is:
[0201]
[0202] During the test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, ... the 100th cycle corresponds to n=100. The battery capacity retention rate data corresponding to Example 1 in Table 1 is the data measured after 300 cycles under the above test conditions, that is, the value of P300.
[0203] Example 1
[0204] 1) Preparation of positive electrode
[0205] The positive electrode active material lithium iron phosphate (particle size D50 = 1.5 μm), conductive carbon black SP, binder PVDF, hydrogenated nitrile rubber, and softener 1 are weighed according to a weight ratio of 97%: 1.5%: 1%: 0.25%: 0.25%, and the hydrogenated nitrile rubber (weight average molecular weight of 200,000, hydrogenation ratio of 50%, molar ratio of acrylonitrile structural unit of 15%) and softener 1 are mixed with an appropriate amount of solvent NMP to make the solid content of 50% to prepare a mixed material, and then the mixed material and the positive electrode active material lithium iron phosphate, conductive carbon black SP and binder PVDF are further dispersed in the solvent NMP, mixed evenly, and a positive electrode slurry is obtained; the positive electrode slurry is evenly coated on the double-sided surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained, wherein the coating amount per unit area on both sides is 0.33 g / 1540.25 mm 2 .
[0206] 2) Preparation of negative electrode
[0207] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed in a mass ratio of 96.4%:0.7%:1.8%:1.1%, and deionized water is added to obtain the negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the double-sided surface of the copper foil; the copper foil is dried at room temperature and then transferred to a 120°C oven for drying for 1h, and then super-cold pressed and cut to obtain the negative electrode sheet, wherein the coating amount per unit area on both sides is 0.17g / 1540.25mm 2 .
[0208] 3) Isolation film
[0209] A 12μm thick polypropylene isolation film was selected.
[0210] 4) Preparation of electrolyte
[0211] The organic solvent is ethylene carbonate (EC) and ethyl methyl carbonate (EMC) mixed evenly in a volume ratio of 3 / 7. In an argon atmosphere glove box with a water content of <10ppm and O2 <0.1ppm, fully dried lithium salt LiPF6 is dissolved in the organic solvent and mixed evenly to obtain an electrolyte. The mass percentage of lithium salt is 12.5%.
[0212] 5) Preparation of batteries
[0213] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound into a square bare battery cell, loaded with an aluminum-plastic film, and then baked at 80°C to remove water, 10g of the corresponding non-aqueous electrolyte is injected, and the mouth is sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a finished lithium-ion battery is obtained.
[0214] The softener 1 used in Example 1 has the following structural characteristics: .
[0215] The lithium ion battery preparation method of Example 2 is similar to that of Example 1, with the main difference being that the softener 2 used replaces the softener 1, and the softener 2 has the following structural characteristics: .
[0216] The softener 2-1 used in Example 2-1 has the following structural characteristics: .
[0217] The softener 2-2 used in Example 2-2 has the following structural characteristics: .
[0218] The softener 2-3 used in Example 2-3 has the following structural characteristics: .
[0219] The lithium ion battery preparation method of Example 3 is similar to that of Example 1, with the main difference being that the softener 3 used replaces the softener 1, and the softener 3 has the following structural characteristics: .
[0220] The lithium ion battery preparation method of Example 4 is similar to that of Example 1, with the main difference being that the softener 4 used replaces the softener 1, and the softener 4 has the following structural characteristics: .
[0221] The lithium ion battery preparation method of Example 5 is similar to that of Example 1, with the main difference being that the softener 5 used replaces the softener 1, and the softener 5 used in the softener 5 has the structural characteristics shown below: .
[0222] The lithium ion battery preparation method of Example 6 is similar to that of Example 1, with the main difference being that the softener 6 used replaces the softener 1, and the softener 6 has the following structural characteristics: .
[0223] The lithium ion battery preparation method of Example 7 is similar to that of Example 1, with the main difference being that the softener 7 used replaces the softener 1, and the softener 7 has the following structural characteristics: .
[0224] The parameters of Examples 1 to 2, 2-1, 2-2, 2-3 and Examples 3 to 7 are summarized in Table 1 below:
[0225] Table 1
[0226]
[0227] The lithium ion battery preparation methods of Examples 8 to 11 are similar to those of Example 1, with the main difference being that different mass ratios of the softener to the hydrogenated nitrile rubber are used, and the total weight percentage of the hydrogenated nitrile rubber and the softener in the positive electrode active layer is controlled to remain unchanged at 0.5%.
[0228] The parameters of Examples 1, 8 to 11 are summarized in Table 2 below:
[0229] Table 2
[0230]
[0231] The lithium ion battery preparation methods of Examples 12 to 17 are similar to those of Example 1, with the main difference being that different weight average molecular weights of hydrogenated nitrile rubbers are used.
[0232] The parameters of Examples 1, 12 to 17 are summarized in Table 3 below:
[0233] Table 3
[0234]
[0235] The lithium ion battery preparation methods of Examples 18 to 20 are similar to those of Example 1, with the main difference being that different hydrogenation ratios of hydrogenated nitrile rubber are used.
[0236] The parameters of Examples 1, 18 to 20 are summarized in Table 4 below:
[0237] Table 4
[0238]
[0239] The lithium ion battery preparation methods of Examples 21 to 24 are similar to those of Example 1, with the main difference being that different molar ratios of acrylonitrile structural units of hydrogenated nitrile rubber are used.
[0240] The parameters of Examples 1, 21 to 24 are summarized in Table 5 below:
[0241] Table 5
[0242]
[0243] The lithium ion battery preparation methods of Examples 25-26 are similar to those of Example 1, with the main difference being that different solid contents of the mixed materials are used.
[0244] The parameters of Examples 1, 25 and 26 are summarized in Table 6 below:
[0245] Table 6
[0246]
[0247] Note: The solid content of the mixed material in Example 26 is 100%, which means that in the step of "1) preparation of positive electrode plate", the hydrogenated nitrile rubber, softener 1, positive electrode active material lithium iron phosphate, conductive carbon black SP and binder PVDF are directly dispersed in the solvent NMP without being mixed with an appropriate amount of solvent NMP in advance.
[0248] The lithium ion battery preparation methods of Examples 27 to 28 are similar to those of Example 1, with the main difference being that different mass percentages of the softener in the positive electrode active layer are used, and the mass percentage of the positive electrode active material in the positive electrode active layer is adjusted accordingly to meet 100%.
[0249] The parameters of Examples 1, 27 and 28 are summarized in Table 7 below:
[0250] Table 7
[0251]
[0252] The preparation method of the lithium ion battery in Comparative Example 1 is similar to that in Example 1, except that the softener 1 is not used, and the mass percentage of the positive electrode active material in the positive electrode active layer is adjusted accordingly to meet 100%.
[0253] The preparation method of the lithium ion battery in Comparative Example 2 is similar to that in Example 1, the main difference being that hydrogenated nitrile rubber is not used, and the mass percentage of the positive electrode active material in the positive electrode active layer is adjusted accordingly to meet 100%.
[0254] The parameters of Example 1 and Comparative Examples 1 and 2 are summarized in Table 8 below:
[0255] Table 8
[0256]
[0257] It can be seen from Tables 1 to 8 that, compared with Comparative Examples 1 to 2, Examples 1 to 28 can reduce the brittleness of the positive electrode sheet, obtain a lower membrane resistance, and improve the first coulombic efficiency and cycle capacity retention rate of the battery.
[0258] From the comparison between Examples 1 to 7, it can be seen that the use of a suitable softener structure can obtain lower brittleness and membrane resistance of the positive electrode sheet, as well as higher first coulombic efficiency and cycle capacity retention rate. Further, from the comparison between Example 2 and Examples 2-1 to 2-3, it can be seen that by reasonably controlling the length of the linear segment (n value) in the softener, lower brittleness and membrane resistance of the positive electrode sheet, as well as higher first coulombic efficiency and cycle capacity retention rate can be obtained.
[0259] From the comparison between Example 1 and Examples 8 to 11, it can be seen that by reasonably controlling the mass ratio of the softener to the hydrogenated nitrile rubber, lower brittleness and membrane resistance of the positive electrode plate, as well as higher first coulomb efficiency and cycle capacity retention rate can be obtained.
[0260] From the comparison between Example 1 and Examples 12 to 17, it can be seen that by reasonably controlling the weight average molecular weight of the hydrogenated nitrile rubber, lower brittleness and membrane resistance of the positive electrode plate, as well as higher first coulomb efficiency and cycle capacity retention rate can be obtained.
[0261] From the comparison between Example 1 and Examples 18 to 20, it can be seen that by reasonably controlling the hydrogenation ratio of the hydrogenated nitrile rubber, lower brittleness and membrane resistance of the positive electrode plate, as well as higher first coulomb efficiency and cycle capacity retention rate can be obtained.
[0262] From the comparison between Example 1 and Examples 21 to 24, it can be seen that by reasonably controlling the molar ratio of the acrylonitrile structural unit in the hydrogenated nitrile rubber, lower brittleness and membrane resistance of the positive electrode plate, as well as higher first coulomb efficiency and cycle capacity retention rate can be obtained.
[0263] From the comparison between Example 1 and Examples 25-26, it can be seen that compared with direct mixing, mixing the materials with the solvent and preparing them into a slurry with a suitable solid content can obtain lower brittleness and membrane resistance of the positive electrode sheet, as well as higher first coulombic efficiency and cycle capacity retention rate.
[0264] From the comparison between Example 1 and Examples 27-28, it can be seen that reasonable control of the proportion of the softener in the positive electrode active layer can obtain lower brittleness and membrane resistance of the positive electrode plate, as well as higher first coulomb efficiency and cycle capacity retention rate.
[0265] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0266] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A lithium-ion battery, comprising a positive electrode plate, characterized in that: The positive electrode plate comprises a positive electrode active layer, and the components of the positive electrode active layer comprise a positive electrode active material, a dispersant and a flexibilizer; the dispersant comprises hydrogenated nitrile rubber, and the flexibilizer comprises a compound containing a linear segment; The linear segment includes a copolymer segment of one or more of a C6-C18 alkyl group, an aryl-O-C6-C36 alkyl group, a polar group-substituted C2-C18 alkyl group, a polar group-substituted-O-C6-C24 alkyl carbon chain, a polyether segment, a polyamine segment, and a polysiloxane segment; The polyether segment has the following structural features: Wherein, R1 each independently includes C1~C18 alkyl or C6~C12 aryl; G1 and G2 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group or a hydroxyl group; 10≤n1≤500; The polyamine segment has the following structural features: Wherein, R2 each independently includes C1~C18 alkyl or C6~C12 aryl; R3 each independently includes H, C1~C18 alkyl or C6~C12 aryl; G3 and G4 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group or an amine group; 10≤n2≤500; The copolymerized segment of the polyamine segment and the polyether segment has the following structural characteristics: Wherein, R4 each independently includes C1~C18 alkyl or C6~C12 aryl; R5 each independently includes H, C1~C18 alkyl or C6~C12 aryl; R6 each independently includes C1~C18 alkyl or C6~C12 aryl; G5 and G6 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group, a hydroxyl group or an amine group; 10≤n3+n4≤500; The polysiloxane segment has the following structural features: Wherein, R7 and R8 each independently include C1~C18 alkyl, C6~C12 aryl, polyether segment or polyoxyethylene ether polyoxypropylene ether copolymer segment; G7 and G8 each independently include a C1~C18 alkyl group, a C6~C12 aryl group, a hydroxyl group or an amine group; 10≤n5≤500。 2. The lithium-ion battery according to claim 1, characterized in that Having at least one of the following characteristics: (1)10≤n1≤50; (2)10≤n2≤50; (3) 10≤n3+n4≤50; (4)10≤n5≤50。 3. The lithium-ion battery according to claim 1, characterized in that The polar groups each independently include one or more of an ester group, an amide group, a carbamate group, a carboxyl group, a hydroxyl group, and an amine group.
4. The lithium ion battery according to any one of claims 1 to 3, characterized in that The mass ratio of the softener to the dispersant is 10:1 to 1:
10.
5. The lithium-ion battery according to claim 4, characterized in that: The mass ratio of the softener to the dispersant is 3:1 to 1:
3.
6. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The hydrogenated nitrile rubber has at least one of the following characteristics (1) to (3): (1) Weight average molecular weight is 500~1000000; (2) The hydrogenation ratio is 10% to 100%; the hydrogenation ratio means: the molar content of double bonds in the nitrile rubber is P1, and the molar content of double bonds in the hydrogenated nitrile rubber obtained after hydrogenation is P2, and the hydrogenation ratio = (P1-P2) / P1; (3) The molar proportion of acrylonitrile structural units is 5%~30%.
7. The lithium-ion battery according to claim 6, characterized in that: The hydrogenated nitrile rubber has at least one of the following characteristics (1) to (3): (1) Weight average molecular weight is 1000~200000; (2) The hydrogenation ratio is 30%~50%; (3) The molar proportion of acrylonitrile structural units is 10%~20%.
8. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The mass percentage of the softener in the positive electrode active layer is 0.05% to 0.5%.
9. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The coating amount per unit area of the positive electrode active layer in the positive electrode sheet is ≥300 mg / 1540.25 mm 2 .
10. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The compaction density of the positive electrode sheet is 3.3 g / cm 3 ~3.6g / cm 3 .
11. The lithium ion battery according to claim 10, characterized in that: The compaction density of the positive electrode sheet is 3.3 g / cm 3 ~3.5g / cm 3 .
12. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The positive electrode active material includes one or more of lithium transition metal oxides and lithium phosphates with an olivine structure.
13. The lithium ion battery according to claim 12, characterized in that: The lithium transition metal oxide includes one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and modified compounds thereof; and / or The lithium-containing phosphate with an olivine structure includes one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
14. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The components of the positive electrode active layer also include a binder.
15. The lithium ion battery according to claim 14, characterized in that: The binder has at least one of the following characteristics (1) to (2): (1) The binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin; (2) In the positive electrode active layer, the mass percentage of the binder is 1% to 2.5%.
16. A method for preparing a lithium ion battery, characterized in that: The preparation steps of the positive electrode active layer include: Mixing components of a positive electrode active layer and a solvent to prepare a positive electrode slurry; the components of the positive electrode active layer include a positive electrode active material, a dispersant and a flexibilizer; the dispersant includes hydrogenated nitrile rubber, and the flexibilizer includes a compound containing a linear segment; Forming the positive electrode slurry to prepare the positive electrode active layer; The linear segment includes a copolymer segment of one or more of a C6-C18 alkyl group, an aryl-O-C6-C36 alkyl group, a polar group-substituted C2-C18 alkyl group, a polar group-substituted-O-C6-C24 alkyl carbon chain, a polyether segment, a polyamine segment, and a polysiloxane segment; The polyether segment has the following structural features: Wherein, R1 each independently includes C1~C18 alkyl or C6~C12 aryl; G1 and G2 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group or a hydroxyl group; 10≤n1≤500; The polyamine segment has the following structural features: Wherein, R2 each independently includes C1~C18 alkyl or C6~C12 aryl; R3 each independently includes H, C1~C18 alkyl or C6~C12 aryl; G3 and G4 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group or an amine group; 10≤n2≤500; The copolymerized segment of the polyamine segment and the polyether segment has the following structural characteristics: Wherein, R4 each independently includes C1~C18 alkyl or C6~C12 aryl; R5 each independently includes H, C1~C18 alkyl or C6~C12 aryl; R6 each independently includes C1~C18 alkyl or C6~C12 aryl; G5 and G6 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group, a hydroxyl group or an amine group; 10≤n3+n4≤500; The polysiloxane segment has the following structural features: Wherein, R7 and R8 each independently include C1~C18 alkyl, C6~C12 aryl, polyether segment or polyoxyethylene ether polyoxypropylene ether copolymer segment; G7 and G8 each independently include a C1~C18 alkyl group, a C6~C12 aryl group, a hydroxyl group or an amine group; 10≤n5≤500。 17. The method for preparing a lithium ion battery according to claim 16, characterized in that: The step of mixing the components of the positive electrode active layer and the solvent comprises: Firstly, the dispersant, the softener and part of the solvent are mixed, and then the obtained mixture is mixed with the remaining components; wherein the solid content of the mixture is 5% to 75%.
18. The method for preparing a lithium ion battery according to claim 17, characterized in that: The solid content of the mixed material is 7% to 20%.
19. A positive electrode plate, characterized in that: The positive electrode plate comprises a positive electrode active layer, and the components of the positive electrode active layer comprise a positive electrode active material, a dispersant and a flexibilizer; the dispersant comprises hydrogenated nitrile rubber, and the flexibilizer comprises a compound containing a linear segment; The linear segment includes a copolymer segment of one or more of a C6-C18 alkyl group, an aryl-O-C6-C36 alkyl group, a polar group-substituted C2-C18 alkyl group, a polar group-substituted-O-C6-C24 alkyl carbon chain, a polyether segment, a polyamine segment, and a polysiloxane segment; The polyether segment has the following structural features: Wherein, R1 each independently includes C1~C18 alkyl or C6~C12 aryl; G1 and G2 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group or a hydroxyl group; 10≤n1≤500; The polyamine segment has the following structural features: Wherein, R2 each independently includes C1~C18 alkyl or C6~C12 aryl; R3 each independently includes H, C1~C18 alkyl or C6~C12 aryl; G3 and G4 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group or an amine group; 10≤n2≤500; The copolymerized segment of the polyamine segment and the polyether segment has the following structural characteristics: Wherein, R4 each independently includes C1~C18 alkyl or C6~C12 aryl; R5 each independently includes H, C1~C18 alkyl or C6~C12 aryl; R6 each independently includes C1~C18 alkyl or C6~C12 aryl; G5 and G6 each independently include a C1~C18 alkyl group, a C6~C18 aryl group, a C1~C18 ester group, a C1~C18 amide group, a C1~C18 carbamate group, a hydroxyl group or an amine group; 10≤n3+n4≤500; The polysiloxane segment has the following structural features: Wherein, R7 and R8 each independently include C1~C18 alkyl, C6~C12 aryl, polyether segment or polyoxyethylene ether polyoxypropylene ether copolymer segment; G7 and G8 each independently include a C1~C18 alkyl group, a C6~C12 aryl group, a hydroxyl group or an amine group; 10≤n5≤500。 20. The positive electrode sheet according to claim 19, characterized in that: The positive electrode sheet in the lithium ion battery according to any one of claims 2 to 15.
21. An electrical device, characterized in that: It comprises at least one of the lithium-ion battery according to any one of claims 1 to 15, the lithium-ion battery prepared by the preparation method according to any one of claims 16 to 18, and the positive electrode sheet according to any one of claims 19 to 20.
Citation Information
Patent Citations
Ternary lithium ion battery composite binder and preparation method thereof
CN116314789A
Positive electrode active material composition, positive electrode sheet, secondary battery, battery module, battery pack, and electric device
CN117642888A
Composition for preparing positive electrode of secondary battery, and positive electrode for secondary battery and secondary battery prepared using the same
KR1020170111749A
Electrode slurry, electrode sheet, secondary battery, and electrical device
WO2024031518A1